On the uniqueness of the variational solution for the problem of equilibrium of the pending drop - Shcherbakov, E.A. (Нелинейные граничные задачи, 2010)
In this paper we study the uniqueness of the equilibrium forms of the axisymmetrical drops pending from the horizontal plane. In our considerations we take into account the intermediate layer separating the liquid phase from that of the vapor.We prove the uniqueness of the variational solution describing the equilibrium forms.